Visible light photoredox catalysis: conversion of a mixture of thiophenols and nitriles into 2-substituted benzothiazoles via consecutive C–S and C–N bond formation reactions. Issue 9 (26th March 2018) - Natarajan, Palani; Manjeet,; Muskan,; Brar, Navpreet Kaur; Jot Kaur, Jaskamal
Abstract : A novel, visible-light-mediated method for the synthesis of 2-substituted benzothiazoles from thiophenols and alkyl/aryl nitriles in the presence of eosin Y under air atmosphere is disclosed. Abstract : A novel, visible-light-mediated method for the construction of 2-substituted benzothiazoles from easily available thiophenols (2.0 equiv.) and alkyl/aryl nitriles (1.0 equiv.) in the presence of eosin Y (0.02 equiv.) under air atmosphere has been developed. The reaction proceeded smoothly, for a wide range of derivatives of thiophenols and nitriles, to give the expected products in moderate to good yields. A reaction mechanism involves the direct oxidative radical coupling of thiophenols with nitriles to afford iminyl radical intermediates giving the expected product by an intramolecular cyclization followed by hydrogen radical loss. To the best of our knowledge, this is the first example of the synthesis of 2-substituted benzothiazoles through sequential C–S and C–N bond formation reactions under photoredox catalysis.